Exploring the Influencing Factors on Breast Self-Examination Among Myanmar Women: A Qualitative Study - Nyein Moh Moh Myint; Nursalam Nursalam; Eka Mishbahatul Mar’ah Has (Jurnal Ners, 2020)
Introduction: Breast self-examination (BSE) is the most sensitive and cost-effective method to diagnose breast cancer at an early stage in healthcare resources’ limited setting. However, the practice of BSE is low in Myanmar. Although various international studies were conducted to clarify the influencing factors in irregular BSE practice, there is a range of different factors and the answer is not yet clear. Hence, this study is aimed to explore the influencing factors on the practice of breast self-examination among Myanmar women.Methods: A qualitative exploratory-descriptive study was conducted on eight women through in-depth semi-structured interviews between February 2020 and March 2020. The samples were women who lived in the rural area of Myanmar and purposive sampling technique was used. Data were analyzed using Colaizzi’s method, which consisted of seven stages.Results: Four themes emerged as the results of the in-depth interview, namely knowledge of breast cancer, knowledge regarding breast self-examination, barriers to performing regular BSE and ways to improve BSE practice.Conclusion: This study showed that the women were inadequate in knowledge and practice regarding BSE and breast cancer. Some barriers of BSE practice are rooted in the inadequate skill of BSE and the women’s attitude.  Greater understanding about breast cancer and improving the confidence of women in BSE will lead to better prognosis. Hence, healthcare authorities and providers should encourage a formal health education program and the results from this study hope to be useful in future rural health education programs of BSE practice.